Study on Vibration Reduction Method for a Subway Station in Soft Ground - Xian-Feng Ma; Ning-Ning Feng; Guo-Bo Wang; Xu Fang (Shock and Vibration)
With the rapid development of metro system in urban areas, vibration and its impact on adjacent structures caused by metro operation have drawn much attention of researches and worries relating to it have risen. This paper analyzed the vibration attenuation and the environment impact by a case study of a subway station in soft ground with adjacent laboratory building. A method of setting a compound separation barrier surrounding the station is checked and different materials used in the barrier have been tried and tested through numerical analysis. Key parameters of the material and the effects of vibration reduction are studied with the purpose that similar methodology and findings can be referenced in future practices.